Geothermal District Heating System for the City of Akureyri in Northern Iceland - Bodvarsson, Gunnar (Geo-Heat Center, Oregon Institiute of Technology, Klamath Falls, OR (USA), 1975)
Preliminary Design of a geothermal district heating system for the City of Akureyri in Northern Iceland has been completed